THE EFFECT OF TARGET DRILL TRAINING ON THE ACCURACY OF THE SABIT KICK OF IPSI GARUT PENCAK SILAT ATHLETES - Indiani Sapitri; Azhar Ramadhana Sonjaya; Alam Hadi Kosasih (Universitas Hamzanwadi, 2026)
Research on improving the accuracy of the sickle kick in pencak silat is still dominated by studies that focus on physical components, while research specifically examining the effectiveness of target-based training remains limited. This study aims to analyze the effect of target drill training on the accuracy of the sickle kick among IPSI pencak silat athletes in Garut Regency. The method used was an experiment with a one-group pretest-posttest design. The sample consisted of 31 athletes selected using total sampling. The instrument used was a 10-second sickle kick skill test. Data were analyzed using descriptive statistics and the Paired Sample T-Test. The results showed a significant improvement between pretest and posttest scores, with a significance level of p < 0.05 and a mean difference of 7.91 points. The improvement occurred across all accuracy zones, with the final category being very high. The conclusion of this study is that target drill exercises are effective in improving the accuracy of the sickle kick. Practically, this method can serve as an alternative for a more targeted technical training strategy in the development of pencak silat athletes.